Lack of Education and Employment Patterns of Poor Urban Women in Rawalpindi City (The Pakistan Development Review, 1989)
Access to education is a key factor for social progress and for reducing the gaps between the various socio-economic groups and sexes. According to the Census of 1981 the literacy rate in Pakistan is 26.5 percent - 35.1 percent for males and 16 percent for females. nliteracy of mothers and other factors lead to low levels of female literacy. The objective of this paper is to show how the lack of education and the consequen t lack of awareness adversely affects the returns to female labour force participation. This paper is based on the data collected in Rawalpindi city for the project "A Socio-economic Profile of Poor Women in Katchi Abadis", and is structured as follows: Section II gives a brief review of the directly relevant sample characteristics and background information on sample selection. Section III provides information on the target group under discussion, i.e., currently earning women, their educational attainments and employment. In Section IV we put together the information proVided in Section III and highlight the payment situation by occupation and educational attainments of the respondents. In Section V·we put forward the advantages of education as perceived by the respondents for themselves and for their daughters. Finally, in Section VI we put forward some conclusions and policy recomrnenda tions.